A study of vertical wind profile of the tropical easterly jet stream over Madras - MOKASHI, R. Y. (MAUSAM, 1970)
Rawin observations for the months June to September during five consecutive year (1961-65) have analysed to study the vertical wind profile of the tropical easterly jet stream over Madras, Visakhapatnam and Trivandrum. The main finding is that the stronger the tropical easterly jet stream, the higher is the altitude of maximum wind. This is just the opposite of the author’s earlier finding in the case of sub-tropical westerly jet stream where stronger the jet maximum the lower is its level of occurrence. It is also seen that the tropical easterly jet strengthens as one towards south from Visakhapatnam to Trivandrum while the level of its occurrence lowers.